La llengua en l’obra narrativa de Carmelina Sánchez-Cutillas: vers la construcció d’un model de referència al País Valencià. - GARCIA SEBASTIÀ, JOSEP VICENT (Scripta, 2021)
This paper describes the linguistic model in Carmelina Sánchez-Cutillas’ prose by means of the analysis of some morphosyntactic, lexical and phonetical spelling uses taken from Matèria de Bretanya and from the short story «El llamp i la sageta de records». The historical-social context in which the author published both texts and the success achieved by Matèria de Bretanya among valencian readers justifies the relevance of examining the linguistic choices of the writer. As we aim at proving, Sánchez-Cutillas chooses to use a model that includes in standard language Valencian forms enjoying prestige due to their learned uses and some dialectisms form the region of the Marina Baixa, without giving up the maximum rapprochement with the rest of local ways of speaking within the linguistic domain. Generally speaking, the model of this writer coincides with that supported by some Valencian grammarians and literary figures of that time, such as Sanchis Guarner or Enric Valor.